Formulasi Strategi Pengembangan Jaringan Distribusi terhadap Tingkat Volume Penjualan : Studi Kasus pada PT Hero Supermarket - Sujana, Sujana; Zuhdi, Saefudin; Kamaludin, Kamaludin (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2006)
The purpose of matrix IE (Internal-External) model is to formulate the company strategy for corporate level to more detail. The result of research indicates that company position is in quadrant V at Matrix IE, that means in the âgrowth and being stableâ position. The EFASâ score is 2,422 and the increasing in market demand is the biggest opportunity factor to achieve by the company. The IFASâ score is 2.719 with inventory control system as a dominant factor (score: 0.452). Thereby the strategy for the company level that can be extended is âdefending and developing strategyâ to increase the volume of sales and companyâs profit... Keywords: Marketing strategy, Distribution network.